Karakteristik Pola Arus di Perairan Teluk Jakarta Pada Musim Barat dan Timur: Characteristichs of Current Pattern in Jakarta Bay in The West and East Monsoons - Nugraha, Teguh; Nurjaya, I Wayan; Rastina; Susanti, Santi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2025)
Jakarta Bay is a coastal area influenced by both natural factors (wind, currents, waves) and human activities (residential areas, coastal development, industry, and resource exploitation). The monsoon phenomenon in the Java Sea affects hydrodynamic patterns, especially current dynamics in Jakarta Bay. This study analyzes changes in current patterns during two distinct monsoon seasons (west and east) in 2021 using a hydrodynamic modeling approach. The model was developed using OpenFlows software with input data including bathymetry, tidal, wind, and wave conditions. Model validation was conducted using tidal and current measurements from field observations in March and August 2021. The results show seasonal variations in current direction and velocity, both in tidal phases and non-tidal (residual) currents. The current patterns aligned with seasonal wind directions, indicating a strong monsoonal influence. Model validation using Root Mean Square Error (RMSE) and Taylor diagram analysis demonstrated good agreement between modeled and observed data, confirming the model's reliability. These hydrodynamic modeling results can serve as a foundation for further studies, such as simulations of pollutant, sediment, and debris dispersion in Jakarta Bay.